2010
DOI: 10.1002/pdi.1456
|View full text |Cite
|
Sign up to set email alerts
|

Non‐attendance at a diabetes transitional clinic and glycaemic control

Abstract: Young patients with diabetes are particularly vulnerable to long‐term complications, and require a carefully planned transition to adult diabetes care. As clinic non‐attendance has been identified as an issue for transitional clinics, we audited our well established clinic to look at non‐attendance rates, and to examine the characteristics of those who miss transitional clinic appointments.We conducted a retrospective analysis of audit data from the diabetes transitional clinic in January to December 2004, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
0
20
1
Order By: Relevance
“…A total of 32 patient factors from 19 studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were identified (Table II). The studies investigated the different patient factors that may affect an individual's willingness and ability to return for followup at their respective health clinics.…”
Section: Patient Factorsmentioning
confidence: 99%
“…A total of 32 patient factors from 19 studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were identified (Table II). The studies investigated the different patient factors that may affect an individual's willingness and ability to return for followup at their respective health clinics.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Young people presenting with higher HbA 1c values (an indicator of long-term glucose control) before transition are less likely to attend adult treatment after leaving paediatric care and have poorly managed diabetes [1,2,10]. Further studies have found that adolescents who were older and met an adult endocrinologist before transition were less likely to be lost to follow-up in the adult clinic [6], suggesting the need for an approach to transition that includes an overlapping of services [2,[11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous recommendations during recent decades, the transfer from paediatric to adult care continues to pose challenges for adolescent patients, their parents and health-care professionals (Jalkut et al, 2009, Masding et al, 2010, McDonagh and Kelly, 2010.…”
Section: Introductionmentioning
confidence: 99%